2000
DOI: 10.1111/j.1600-0684.2000.290605.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in daily sperm production rate of rhesus and bonnet monkeys

Abstract: Daily sperm production (DSP) rate was estimated in adult male rhesus and bonnet monkeys to evaluate seasonal changes in the gametogenic activity of the testes. Three monkeys of each species were castrated during breeding and non-breeding seasons and DSP rate was estimated by enumerating the homogenization-resistant spermatid nuclei of steps 13 and 14. Results indicated a significant reduction in the DSP rate per testis during the non-breeding season in two species, along with a marked decline in the testis wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 6 publications
0
13
2
Order By: Relevance
“…These observations suggest that the testis in this animal is vulnerable to change in its natural environmental temperature, however, in terms of seasonal variation of spermatogenesis in M. radiata it was less affected than M. mulatta (Gupta et al 2000), and these above mentioned anatomical and behavioural adaptations could be playing a major role in this outcome. This was evident from the histology of the testis from new entry from the wild to the colony during the non-breeding season (n = 2).…”
Section: Male Reproductive System In Bonnet Monkey 57mentioning
confidence: 60%
“…These observations suggest that the testis in this animal is vulnerable to change in its natural environmental temperature, however, in terms of seasonal variation of spermatogenesis in M. radiata it was less affected than M. mulatta (Gupta et al 2000), and these above mentioned anatomical and behavioural adaptations could be playing a major role in this outcome. This was evident from the histology of the testis from new entry from the wild to the colony during the non-breeding season (n = 2).…”
Section: Male Reproductive System In Bonnet Monkey 57mentioning
confidence: 60%
“…7, top). In this regard, it is noteworthy that adult rodent and adult rhesus testes both produce a similar number of sperm per gram of testis per day (Sharpe, 1994; Gupta et al ., 2000; Thayer et al ., 2001). Therefore it may be concluded that the stem/progenitor cell pools in primates and rodents employ different strategies to meet a similar biological demand.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the large SSC pool, the relative size of the progenitor pool (GFRα1 + , PLZF + , NGN3 + , cKIT − ) appeared much smaller in adult macaques than in rodents. Thus, it appears that rodents and primates employ different strategies to meet a similar biological demand [adult rodent and adult rhesus testes have similar sperm output per gram of testis per day (Sharpe 1994; Gupta et al 2000; Thayer et al 2001)]. Rodents may have few SSCs and more transit-amplifying progenitors while rhesus testes may have more SSCs and fewer transit-amplifying progenitors.…”
Section: Marker Analysis For Functional Categorization Of Rhesus Smentioning
confidence: 99%